Transition from open-pit to underground – using Integer Programming considering grade uncertainty - Chung, Joyce Sze Yee; Topal, Erkan; Erten, Oktay (2015)
The determination of transition point from open-pit (OP) to underground (UG) is one of the most challenging mining engineering problems. The shallow deposits which vertically extend to considerable depth will have potential to make the transition from OP to UG. In this paper, Mixed Integer Programming (MIP), a well-known operation research technique is introduced to solve the transition problem. Conditional simulation is utilised to generate realisations of the resource model. Thus, the utilisation of the simulated realisations will reduce the geological uncertainty and risk. The aim of this paper is to incorporate MIP model and conditional simulation technique to optimise the transition from OP to UG. As a result, a ‘Transition Envelope’ which represents a zone where the transition might occur is formed.